Ecological Implications of Plant Secondary Metabolites - Phytochemical Diversity Can Enhance Agricultural Sustainability - Clemensen, Andrea K.; Provenza, Frederick D.; Hendrickson, John R.; Grusak, Michael A. (Frontiers in Sustainable Food Systems, 2020)
Conventional agriculture production, although proficient in feeding an expanding human population, is having negative environmental impacts that are diminishing the sustainability of natural resources. Producers and consumers are increasingly interested in understanding how land management practices can enhance agricultural sustainability and improve human health. This perspective article offers a new approach to enhancing agricultural sustainability by growing crops and forages with diverse plant secondary metabolites (PSMs). Plants produce tens of thousands of PSMs to mediate interactions with soil, other plants, and animals. Plants use these metabolites to communicate with organisms in their environment, both above and belowground, and to modify the rhizosphere and influence chemical, physical, and biological attributes of soil. In pastures and rangelands, animal health benefits and production increases when animals ingest forages with different PSMs, which has implications for enhancing the biochemical richness of meat and dairy products for human consumption. A deeper understanding of PSMs, and their functional roles in agroecology, may help producers better manage their lands, reduce inputs, and minimize negative environmental impacts.